Design of a flexible component gathering algorithm for converting cell-based models to graph representations for use in evolutionary search. - Budnikova, Marianna.; Habig, Jeffrey W.; Lobo, Daniel.; Cornia, Nicolas.; Levin, Michael.; Andersen, Tim. (2016)
Background: The ability of science to produce experimental data has outpaced the ability to effectively visualize and integrate the data into a conceptual framework that can further higher order understanding. Multidimensional and shape-based observational data of regenerative biology presents a particularly daunting challenge in this regard. Large amounts of data are available in regenerative biology, but little progress has been made in understanding how organisms such as planaria robustly achieve and maintain body form. An example of this kind of data can be found in a new repository (PlanformDB) that encodes descriptions of planaria experiments and morphological outcomes using a graph formalism.; Springer Open.